Adherence to 24-hr Activity Guidelines and Quality of Life in Singapore Children: A Self-Reported Survey Study (ACPES (ASEAN Council of Physical Education and Sport) in cooperation with Universitas Negeri Semarang (UNNES), 2023)
There are limited data on how the lifestyle behaviours of school-aged children in Singapore fare against the Singapore Integrated 24-hr Activity Guidelines. One hundred and thirty-eight children ages 9 to 13 years self-reported their recreational screen time, moderate-to-vigorous physical activity (MVPA), night-time sleep duration, and health-related Quality of Life (HRQoL) in a survey package. Their lifestyle behaviours were then benchmarked against the Singapore Integrated 24-hr Activity Guidelines recommendations, specifically, (i) at least 1 hr/day of MVPA, (ii) no more than 2 hr/day of recreational screen time, and 7-9 hr/day of sleep. Association between the number of guideline recommendations met and HRQoL z-scores were explored. Of the 138 children, 6.5% met all three guideline recommendations while 29.0% did not meet any guideline recommendations. MVPA guideline recommendation was least adhered to followed by recreational screen time and sleep. The number of guideline recommendations met was significantly associated with children’s HRQoL, with an increase of 0.289 in HRQoL z-score (5.9%) for every additional guideline met. The 24-hr activity behaviours of Singapore children was sub-optimal in which the proportion of children who did not meet any guideline recommendations is higher than those who met all guideline recommendations. Nonetheless, larger cohort studies are needed to establish its prevalence. Greater dissemination of the guidelines and ameliorative programs targeted at different groups of children should be made to help support children in adopting healthy lifestyle habits.